TUTORIAL: ION ACTIVATION IN TANDEM MASS SPECTROMETRY USING ULTRA‐HIGH RESOLUTION INSTRUMENTATION. Issue 5 (11th February 2020) - Bayat, Parisa; Lesage, Denis; Cole, Richard B.
Abstract : Tandem mass spectrometry involves isolation of specific precursor ions and their subsequent excitation through collision‐, photon‐, or electron‐mediated activation techniques in order to induce unimolecular dissociation leading to formation of fragment ions. These powerful ion activation techniques, typically used in between mass selection and mass analysis steps for structural elucidation, have not only found a wide variety of analytical applications in chemistry and biology, but they have also been used to study the fundamental properties of ions in the gas phase. In this tutorial paper, a brief overview is presented of the theories that have been used to describe the activation of ions and their subsequent unimolecular dissociation. Acronyms of the presented techniques include CID, PQD, HCD, SORI, SID, BIRD, IRMPD, UVPD, EPD, ECD, EDD, ETD, and EID. The fundamental principles of these techniques are discussed in the context of their implementation on ultra‐high resolution tandem mass spectrometers. © 2020 John Wiley & Sons Ltd. Mass Spec Rev